2017
DOI: 10.1007/s00442-017-3995-0
|View full text |Cite
|
Sign up to set email alerts
|

Predator–prey interaction reveals local effects of high-altitude insect migration

Abstract: High-altitude nocturnal insect migrations are ubiquitous and represent significant pulses of biomass, which impact large areas and multiple trophic levels, yet are difficult to study and poorly understood. Predation on migratory insects by high-flying bats provides potential for investigating flows of migratory insects across a landscape. Brazilian free-tailed bats, Tadarida brasiliensis, provide valuable ecosystem services by consuming migratory pests, and research suggests migratory insects are an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 47 publications
5
56
0
3
Order By: Relevance
“…Although insectivorous bats are considered to be the main predators of arthropod pests (reviewed in Riccucci & Lanza, ), actual measures of the incidence of crop pest insects within the diet of bat species have been seldom studied (but see Krauel et al., ), principally because the molecular techniques that allow species‐level identification of prey items have only recently been developed (Bohmann et al., ). In this study, we merged DNA metabarcoding of faecal samples with spatial analyses to show that (i) the insectivorous bat Miniopterus schreibersii consumes a great variety of pest arthropods that affect different crops across the continent and (ii) the dietary niche of the species reflects habitat modification due to intensive farming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although insectivorous bats are considered to be the main predators of arthropod pests (reviewed in Riccucci & Lanza, ), actual measures of the incidence of crop pest insects within the diet of bat species have been seldom studied (but see Krauel et al., ), principally because the molecular techniques that allow species‐level identification of prey items have only recently been developed (Bohmann et al., ). In this study, we merged DNA metabarcoding of faecal samples with spatial analyses to show that (i) the insectivorous bat Miniopterus schreibersii consumes a great variety of pest arthropods that affect different crops across the continent and (ii) the dietary niche of the species reflects habitat modification due to intensive farming.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been successfully used to study sexual and seasonal variation in bat diet (Mata et al., 2016 ; Vesterinen et al., ), predator–prey interactions (Clare, Fraser, Braid, Fenton, & Hebert, ; Dodd, Chapman, Harwood, Lacki, & Rieske, ) and resource partitioning (Bohmann et al., ; Razgour et al., ), among others. Although geographically localized DNA metabarcoding studies have revealed some bat populations occasionally (e.g., Razgour et al., ; Vesterinen et al., ) or regularly (e.g., Krauel, Brown, Westbrook, & McCracken, ) consume crop pest species, no previous study has shown the incidence of pest species in the dietary niche of a species across a whole continent.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, conventional methods to study their diets hardly deliver the taxonomic resolution required for this task (Boyles et al, 2013; Clare, Fraser, Braid, Fenton, & Hebert, 2009; Kunz et al, 2011; Whitaker, 1988). DNA metabarcoding (Pompanon et al, 2012; Taberlet, Coissac, Pompanon, Brochmann, & Willerslev, 2012) overcomes this limitation and is applied to amplify and sequence taxonomically informative DNA markers from traces of arthropod prey in bat faeces while processing multiple samples simultaneously to eventually identify various bat prey taxa to species (Bohmann et al, 2011; Razgour et al, 2011; Zeale, Butlin, Barker, Lees, & Jones, 2011)—thus, demonstrating that certain bat species consume numerous pest species (Aizpurua et al, 2018; Galan et al, 2018; Krauel, Brown, Westbrook, & Mccracken, 2018). The rapid decrease in sequencing costs and the improved methodologies for conducting metabarcoding diet studies (Alberdi, Aizpurua, Gilbert, & Bohmann, 2018) constitute a unique tool with which to assess potential ecosystem services by various species of bats and address their relevance to CBC (Gurr & You, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we evaluate how variability among (a) individual bats, (b) faecal pellets of each bat and (c) PCRs of each pellet affect estimates of diet diversity and composition and on the frequency of occurrence of the prey items. Also, we tested the effects of analysing pools of samples vs. separate samples per individual, as these two variants are often used in dietary studies (e.g., pools : Burgar et al., ; Clare et al., 2014a, 2014b; Krauel, Brown, Westbrook, & McCracken, ; individuals : Hope et al., ; Mata et al., ; Vesterinen, Lilley, Laine, & Wahlberg, ). Our results were used to analyse the level of replication required to obtain accurate descriptions of predator diets using metabarcoding.…”
Section: Introductionmentioning
confidence: 99%